En Tierras de Hércules. Torregorda - Camposoto - Sancti Petri Una Revisión del Patrimonio - Bruquetas-Galán, Carlos (2023)
En tierras de Hércules explores the history and archaeological heritage of the southwest coast of the Isla Gaditana - the territory where the Temple of Hercules and the Idol of Cádiz are said to have stood for more than twelve centuries: Torregorda, Camposoto and Sancti Petri.The text examines the occupation sequence of Palaeolithic, Neolithic, Bronze-Age and historic societies in the area. In addition, it analyses the shaping of the landscape by geological, sedimentary and human action since the Phoenician settlement. The historical region of the Strait of Gibraltar, considered the end of the 'known world' until the modern age, is studied as an intercontinental and cultural bridge.The core of the work is an examination of 32 groups of remains, classified according to communicational, strategic and environmental factors. This includes those relating to the underwater site of the Sancti Petri Castle, which are usually associated with the Temple of Hercules. Using manuscripts from local archives, the book documents elements such as the emergence of the underwater remains of the Temple of Hercules or the construction of canals and defensive architecture. And by means of prehistoric rock art, it examines the origins of sailing in the vicinity of Gibraltar. A final chapter recommends the investigation of the millenary intersection between the Rio Arillo channel and the Calzada de La Alcantarilla road.